Impact of Management Strategies on Corporate Performance of Selected Enterprises in Kano State, Nigeria - Musa, Zakari; Tijjani Abdurrahaman, Daha; Terhile Tyohen, James (Acta Universitatis Danubius. Œconomica, 2024)
This study analysed the impact of strategic management on the profitability of selected enterprises in Kano State, Nigeria. Kano State's five largest publicly traded manufacturers were chosen. Primary data were collected via a questionnaire given to 330 randomly picked employees at the selected companies. Data for the study were analysed using ANOVA, correlation, and descriptive statistics. Management strategies were found to have a substantial influence on the corporate performance and profitability of some selected enterprises in Kano State. Management strategies also correlated positively with the degree to which enterprises faced competition. The results of this research indicate that management strategies have a crucial role in improving enterprise output in Kano State. The study concludes that Nigerian enterprises of all sizes should place a premium on management strategies, policies, and practises. The study has revealed the significant and multi-faceted impact of management strategy decisions, management policies, and management strategic programmes on the operational performance and profitability of enterprises in Kano State. The findings underscore the pivotal role of effective management strategies in shaping an organization's competitive advantage, resilience, and growth prospects in a dynamic enterprise environment. The study recommends that managers should invest more in management strategies and programmes that encourage creativity, progress, and adaptability. Evaluation and refinement of these programmes regularly are necessary to maintain their usefulness and currency.